2015
DOI: 10.1176/appi.focus.130118
|View full text |Cite
|
Sign up to set email alerts
|

Early Intervention for Symptomatic Youth at Risk for Bipolar Disorder: A Randomized Trial of Family-Focused Therapy

Abstract: DisclosuresDr. Miklowitz has received research funding from the National Institute of Mental Health (NIMH), the National Association for Research on Schizophrenia and Depression (NARSAD), the Danny Alberts Foundation, the Attias Family Foundation, and the Robert L. Sutherland Foundation; and royalties from Guilford Press and John Wiley and Sons. Dr. Schneck has received funding from the Crowne Family Foundation. Dr. Cosgrove has received funding from the Lucille Packard Foundation for Children's Health, Spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 35 publications
3
79
0
2
Order By: Relevance
“…For instance, collectivism may slow personal recovery when the family is ashamed by the stigma associated with mental illness [22,23]. Sadly, family interactions may exert negative social control over people diagnosed with mental illness [24,25]. In order to understand how I-C is related to recovery, this section highlights five important features about the concepts of IVO and CVO.…”
Section: Unpacking Individualism and Collectivismmentioning
confidence: 99%
“…For instance, collectivism may slow personal recovery when the family is ashamed by the stigma associated with mental illness [22,23]. Sadly, family interactions may exert negative social control over people diagnosed with mental illness [24,25]. In order to understand how I-C is related to recovery, this section highlights five important features about the concepts of IVO and CVO.…”
Section: Unpacking Individualism and Collectivismmentioning
confidence: 99%
“…One example may be interventions at the level of the family, who may then be able to better care for a child over the course of his or her development. Miklowitz et al (2013) describe more rapid recovery from mood symptoms and more weeks without mood symptoms in children at familial risk of bipolar disorder randomized to family-focused psychotherapy in comparison with a control group. Early treatment approaches in ASD often include parent training that promotes use of new skills in the home setting.…”
Section: The Potential For Arresting Cascades Of Emerging Symptoms Acmentioning
confidence: 93%
“…89 Two randomised controlled trials including symptomatic patients with bipolar I and II found that, in the 1-2 years after a manic, mixed, or depressive episode, patients with bipolar disorder who received familyfocused therapy and pharma cotherapy had 30-35% lower rates of relapse and rehospitalisation and less severe symptoms than did patients in case manage ment 28 or equally intensive individual treatment. 63 Two randomised controlled trials in paediatric populations-one in adolescents (aged 12-18 years) with bipolar disorder 64 and one in children and adolescents (aged 9-17 years) with depression or hypomania with a first degree relative with bipolar disorder 65 -found that children and adolescents who received familyfocused therapy and pharmacotherapy recovered more rapidly from depressive episodes (HR 0·37-0·54) than did children and adolescents in brief psychoeducation and pharmacotherapy.…”
Section: Family-focused Therapymentioning
confidence: 99%
“…One small randomised trial found that family-focused therapy was more effective than usual care in the treatment of hypomanic and depressive symptoms in young people (aged 9-17 years) with a first-degree bipolar relative. 65 Whether early pharma cological or psychosocial interventions for prodromal youth can help to delay or prevent the transition to bipolar disorder types I or II in adulthood will be crucial to investigate in this decade.…”
Section: Future Directionsmentioning
confidence: 99%